Detection of Precipitating Factors of Hepatic Encephalopathy in Chronic Liver Disease Patients in a Tertiary Hospital (Journal of Medicine, 2017)
Background: Chronic liver disease (CLD) is commonly encountered by physicians in hospital practice. Hepatic encephalopathy is a serious complication of chronic liver disease, arising most commonly in those with advanced liver cirrhosis. In patients with otherwise stable cirrhosis, hepatic encephalopathy often follows clearly identifiable precipitating events. The aim of study is to find out the precipitating factors and their frequency in patients of CLD presenting with hepatic encephalopathy to prevent mortality and morbidity.Methods: This descriptive observational study was carried out to identify the precipitating factors and their frequency among 50 cases of diagnosed chronic liver disease presenting with hepatic encephalopathy at department of Medicine of Sir Salimullah Medical College & Mitford hospital, Dhaka from July 2012 to December 2012 for a period of 6 months.Results: Among 50 patients, 36 patients (72%) were male, 14 (28%) were female. Study showed that age frequency 14 (28%) were from 41-50 years and 08 (16%) were from 51-60 years, 12 (24%) >60 years of age. Out of 50 patients, the etiology of liver cirrhosis was hepatitis B virus in 28 (56%), hepatitis C virus in 4 (8%), both Hepatitis B & C in 02 (4%) Among 50 patients, 13 (26%)were in Grade-3 and 11 (22%) in Grade-2 Hepatic encephalopathy. According to Child-Pugh scoring 16 (32%) in Grade-C & 09 (18%) in Grade-B. The most common precipitating factors were identified as GI bleeding (28%), Infection (26%), mixed (16%) & unknown (20%). In this study, mortality rate was 32% most of the patients from Child-Pugh class-C.Conclusions: Commonest precipitating factors of hepatic encephalopathy in this study were upper G.I. bleeding, infection, mixed factor and electrolyte imbalance. To prevent hepatic encephalopathy caution must be exercised in putting chronic liver disease patient on diuretics. Early and effective infection control measures and better hygienic conditions in government hospitals are needed to be maintained.J MEDICINE Jan 2018; 19 (1) : 10-14